Headlong - Frayn, Michael (London : Faber and Faber, 1999)
A young art historian sees the chance of a lifetime as he seeks a treasure which is in someone else's possession. His venture becomes a kind of detective story and a painful moral and social comedy
Keywords: English fiction; Painting -- fiction